Efektifitas Investigasi Insiden - Fuadi, Yan; Hardiyono, Hardiyono; Ananta, Erwin; Siboro, Impol (EUNOIA, 2022)
Work accidents are unexpected and unexpected events. Unexpected, because behind the incident there was no intentional element, especially in the form of planning. OSH efforts in preventing accidents Accident Investigation is one of the inspection activities in the workplace specifically, which is carried out after an accident or incident that causes suffering to humans and results in loss and damage to property/property and other company assets. Work accidents that occur can cause losses, both for the workers themselves and for the company. Losses received by workers can be in the form of illness, disability or even loss of life. The target that we will achieve related to the implementation of this community service is to provide knowledge for workers who work in the company about the importance of hazards and risks in the workplace, to increase knowledge for companies in order to prevent accidents at work in the company